Retrospective analysis of patients underwent colonoscopic polypectomy: A two-center study - Fatih Kamis; Alpaslan Tanoglu; Ece Unal Cetin; Yavuz Beyazit; Yusuf Yazgan (Medicine Science, 2020)
Colonoscopy is a widely used modality for detecting colonic pathologies nearly all over the world. In this retrospective analysis, we aimed to determine the prevalence of colonic polyps and their histopathological results based on colonoscopies performed in the gastroenterology unit in Canakkale Onsekiz Mart University Health Practice and Research Hospital and Istanbul Sultan Abdulhamidhan Training and Research Hospital. Patients underwent colonoscopic examination due to lower gastrointestinal system complaints between 01/01/2014 and 01/12/2019 were evaluated. Patient age, gender, indications, colonoscopic findings, polyp number, size and histopathologic results of the lesions were recorded. A total of 1040 polyps were detected from 839 polypectomy operations performed according to the colonoscopic evaluation of 9044 patients between January 2014 and January 2019. Bleeding after polypectomy was observed in 8 (0.95%) patients and all of the bleedings were controlled with sclerotherapy and/or heater probe coagulation. According to the polyp detection sites, rectosigmoid region (49.7%) was followed by transverse colon (17.3%), descending colon (17.5%), ascending colon (10.5%) and caecum (5%). Adenomatous polyps were the most encountered histopathologic type followed by hyperplastic polyps (19.6%). Thirteen (1.25%) polyps were reported as adenocarcinoma. Polypectomy is an effective procedure of colonoscopy when performed by expert hands. In this retrospective analysis, our results was found to be consistent with those of the literature in terms of polyp number, size and histopathologic characteristics. [Med-Science 2020; 9(2.000): 473-7]